ANALYSING TRENDS AND CORRELATIONS FROM INTERNET SEARCHES: CASE STUDY OF ROMANIA - Popescu, Mioara (Annales Universitatis Apulensis Series Oeconomica; Vol 1 No 19 (2017): Annales Universitatis Apulensis Series Oeconomica, 2017)
In the recent years, the scientific community explored the possibility to use the publicly available web searches volume histories from search engines together with time-series analysis to forecast and analyse, among other things, travel decisions in specific countries. In this study, we use their approach in a specific case study for Romania, by using query-specific search data to analyse the correlations with other keywords and the seasonality and geographic distribution of the historical online searches. We analyse a data set consisting of searches performed from 2014-2017 using specific keywords. Based on this approach, interesting correlations with different keywords are revealed by those tools. Moreover, we can observe a historical change in the queries performed, which reveal interesting facts about a change of behaviour.